Geographic differences in therapy for stage I non‐small‐cell lung cancer in older adults. Issue 6 (31st January 2022) - Dezube, Aaron R.; Mazzola, Emanuele; Cooper, Lisa; Deeb, Ashley L.; De‐Leon, Luis E.; Singer, Lisa; Jacobson, Francine L.; Jaklitsch, Michael T.; Wiener, Daniel
Abstract: Background: Geographic and socioeconomic factors impact patient treatment choices for certain cancers. Whether they impact treatment in older adults with lung cancer is unknown. We investigated geographic differences in treatment for stage I non‐small‐cell lung cancer (NSCLC) in older adults in the United States. Methods: Using the Surveillance, Epidemiology and End Results Database 18th submission, a cohort of stage I NSCLC patients ≥60‐years‐old was created. Treatment differences (surgery or radiation alone) by geographic location and socioeconomic factors were analyzed. Results: Forty‐three thousand three hundred and eighty‐seven stage I NSCLC patients were analyzed. Demographics and socioeconomic factors varied across all 13 states ( p < 0.001). Surgery was the most common treatment in all states (range 58.6% in AK to 86.5% in CT) (all p < 0.001). Our multivariable analysis found older individuals had higher odds of getting radiation as compared to surgery (odds ratio [OR]: 1.22 for 65–69 years‐old to OR: 8.95 for 85+ years‐old; p < 0.001). Multiple states (LA, HI, IA, MI, WA, NM) were associated with increased odds of radiation use (vs. surgery alone) (all p < 0.05). People with lower education level (OR: 0.98) and median income (OR: 0.99) and non‐Black race (OR: 0.52 for "other" to OR: 0.68 for "White" race with respect to Black race) were associated with lower odds of radiation ( p < 0.05). Conclusions: Our study identified treatment differences for stage I NSCLC patients in the United States related to demographics, socioeconomic factors, and geographic location.